Advanced engineering and technology : proceedings of the 2014 Annual Congress on Advanced Engineering and Technology (CAET 2014), Hong Kong, 19-20 April 2014 - Annual Congress on Advanced Engineering and Technology (CAET) (2014 : Hong Kong); Xie, Liquan, 1972-, editor; Huang, Dianjian, editor (Leiden, The Netherlands : CRC Press/Balkema, 2014)
Includes bibliographical references and index